2017
DOI: 10.1111/imj.13511
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic complications during the treatment of Mycobacterium ulcerans disease in Australian patients

Abstract: Severe antibiotic complications during M. ulcerans treatment are high with increased rates independently associated with reduced renal function and female gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, based on our published experience of successful outcomes with the combination of surgery and shortened antibiotic treatment durations,[ 17 ] in this study we found that both of these above surgical options have the additional advantage of permitting significantly shorter antibiotic courses (an average reduction of half the duration) to be used without affecting treatment success rates, with the potential to reduce antibiotic related treatment toxicity. [ 18 ] Therefore this provides clinicians in settings with access to appropriate surgical services an additional treatment option to antibiotics alone for small lesions that may reduce healing times and antibiotic toxicity. Surgical debridement was not associated with reduced healing times, but any beneficial effect may have been confounded by the fact that the majority of cases where it was used (75%) also experienced paradoxical reactions which would have biased the sample towards prolonged healing.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our published experience of successful outcomes with the combination of surgery and shortened antibiotic treatment durations,[ 17 ] in this study we found that both of these above surgical options have the additional advantage of permitting significantly shorter antibiotic courses (an average reduction of half the duration) to be used without affecting treatment success rates, with the potential to reduce antibiotic related treatment toxicity. [ 18 ] Therefore this provides clinicians in settings with access to appropriate surgical services an additional treatment option to antibiotics alone for small lesions that may reduce healing times and antibiotic toxicity. Surgical debridement was not associated with reduced healing times, but any beneficial effect may have been confounded by the fact that the majority of cases where it was used (75%) also experienced paradoxical reactions which would have biased the sample towards prolonged healing.…”
Section: Discussionmentioning
confidence: 99%
“…Although ototoxicity and other complications of STR treatment were not initially observed in West African patients based on self-report, more objective audiometric testing showed that hearing loss does indeed occur [ 4 ]. In Australia, which also has a large number of cases, all-oral antibiotic therapy combined with surgery has been in practice for many years [ 5 ]. In March of 2017, the BU Technical Advisory Group for the World Health Organization Global BU Initiative, due to difficulties in obtaining STR and preliminary findings of non-inferiority in a clinical trial (NCT01659437) in West Africa, recommended replacing STR with oral clarithromycin (CLR, 15–30 mg/kg) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ATP synthase inhibitor bedaquiline (BDQ) has significant treatment-shortening effects in mouse TB models and is a core component of novel treatment-shortening regimens for both drug-susceptible and multidrug-resistant TB (10)(11)(12)(13)(14)(15)(16). The cytochrome bc 1 :aa 3 complex inhibitor Q203 has efficacy in mouse TB models and is poised to enter phase 2 trials in TB patients (17,18). Clofazimine is reduced by NDH-2 (type II dehydrogenase), which is the point of entry of electrons into the respiratory chain (9,19).…”
mentioning
confidence: 99%